PERGESERAN TATA CARA ADAT PERKAWINAN MINANGKBAU DI NAGARI LAWANG KECAMATAN MATUR KABUPATEN AGAM SUMATERA BARAT - Wahyuni, Sartika Wahyuni Sartika; Ibrahim, Bedriati Ibrahim Bedriati; Melay, Ridwan Melay Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The customs are embraced behavior is hereditary and is valid for a long time that the rules are strict and binding. Customs of the peoples are very various one customs in Minangkabau is customary marriages, which have certain rules and regulations determined by local custom. Minangkabau marriage does not create a new core life, as husband and wife remain a member of their lineage respectively. The purpose of this study to determine the procedure of customary marriage Minangkabau society in Nagari Lawang Subdistrict Matur Agam regency of West Sumatra, to know the shapes shift in traditional wedding Minangkabau society in Nagari Lawang Subdistrict Matur Agam regency of West Sumatra, to determine the factors that cause a shift procedure of customary marriage Minangkabau society in Nagari Lawang Subdistrict Matur Agam regency of West Sumatra, to determine whether there are effort Minangkabau society in Nagari Lawang Subdistrict Matur Agam regency of West Sumatra in preserving traditional marriage has undergone a shift, to compare the procedures of customary marriage Minangkabau people , The method used is descriptive qualitative, where data are collected through interviews, observation, documentation, and Library Studies. Data was analyzed using qualitative way. When the study began filing title until the completion of a revised proposal last essay writer. The results showed that the customary marriage ordinance in Lawang Nagar is still held up to now. However, there are procedures for the customary marriage of a shift in its implementation. The shift in the way customs perakawinan itself is caused by a factor of technological progress, modernization, economic factors, globalization. Minangkabau society efforts in Nagari Lawang play a huge role in addressing and improving the procedures for sifting customs shift.Keywords: Shift, Indigenous, Marriage